Upscaling Multiphase Flow in Porous Media From Pore to Core and Beyond - Das, D.B.; Hassanizadeh, S.M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
This book provides concise, up-to-date and easy-to-follow information on certain aspects of an ever important research area: multiphase flow in porous media. This flow type is of great significance in many petroleum and environmental engineering problems, such as in secondary and tertiary oil recovery, subsurface remediation and CO2 sequestration. This book contains a collection of selected papers (all refereed) from a number of well-known experts on multiphase flow. The papers describe both recent and state-of-the-art modeling and experimental techniques for study of multiphase flow phenomena in porous media. Specifically, the book analyses three advanced topics: upscaling, pore-scale modeling, and dynamic effects in multiphase flow in porous media. This will be an invaluable reference for the development of new theories and computer-based modeling techniques for solving realistic multiphase flow problems. Part of this book has already been published in a journal. Audience This book will be of interest to academics, researchers and consultants working in the area of flow in porous media.
Pore Scale Network Modelling -- Bundle-of-Tubes Model for Calculating Dynamic Effects in the Capillary-Pressure-Saturation Relationship -- Predictive Pore-Scale Modeling of Single and Multiphase Flow -- Digitally Reconstructed Porous Media: Transport and Sorption Properties -- Pore-Network Modeling of Isothermal Drying in Porous Media -- Phenomenological Meniscus Model for Two-Phase Flows in Porous Media -- Editorial -- Dynamic Effects and Continuum-Scale Modelling -- Macro-Scale Dynamic Effects in Homogeneous and Heterogeneous Porous Media -- Dynamic Capillary Pressure Mechanism for Instability in Gravity-Driven Flows; Review and Extension to Very Dry Conditions -- Analytic Analysis for Oil Recovery During Counter-Current Imbibition in Strongly Water-Wet Systems -- Multi-Stage Upscaling: Selection of Suitable Methods -- Dynamic Effects in Multiphase Flow: A Pore-scale Network Approach -- Upscaling of Two-Phase Flow Processes in Porous Media.
Keywords: Earth sciences; Hydrology; Hydrogeology; Computer mathematics; Fluid mechanics; Earth Sciences; Hydrogeology; Hydrology/Water Resources; Environmental Monitoring/Analysis.; Engineering Fluid Dynamics; Computational Mathematics and Numerical Analysis; Earth Sciences, general; Electronic books